1997
DOI: 10.1192/bjp.171.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of psychological debriefing for victims of acute burn trauma

Abstract: This study seriously questions the wisdom of advocating one-off interventions post-trauma, and should stimulate research into more effective initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
286
2
21

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(322 citation statements)
references
References 10 publications
11
286
2
21
Order By: Relevance
“…However, several studies showed a worsening in the debriefing groups when compared to a control group (Bisson et al 1997;Deahl et al 2000;Hobbs et al 1996;Mayou et al 2000), while two studies did not show a difference (Conlon et al 1999;Rose et al 1999). Also, a metaanalysis of debriefing showed that it does not improve natural recovery from trauma-related disorders (van Emmerik et al 2002).…”
Section: Prevention Of Ptsdmentioning
confidence: 99%
“…However, several studies showed a worsening in the debriefing groups when compared to a control group (Bisson et al 1997;Deahl et al 2000;Hobbs et al 1996;Mayou et al 2000), while two studies did not show a difference (Conlon et al 1999;Rose et al 1999). Also, a metaanalysis of debriefing showed that it does not improve natural recovery from trauma-related disorders (van Emmerik et al 2002).…”
Section: Prevention Of Ptsdmentioning
confidence: 99%
“…A systematic review of the extensive literature on posttraumatic debriefing concluded that individuals exposed to psychological debriefing programs are just as likely to develop PTSD as individuals who do not participate (Rose et al, 2002). In fact, two rigorous evaluations found that debriefing was associated with an increased risk of PTSD (Bisson et al, 1997;Hobbs et al, 1996). At this date, researchers and clinical practice guidelines recommend that civilian-style debriefing programs not be offered to trauma survivors (U.S. Department of Veterans Affairs and U.S. Department of Defense, 2010;McNally, Bryant, and Ehlers, 2003;Nash and Watson, 2011;Rose et al, 2002).…”
Section: Key Findings Lessons From Similar Programsmentioning
confidence: 99%
“…Individuals exposed to a trauma who received a debriefing intervention were just as likely to develop PTSD as individuals who received either no intervention or an educational intervention. In fact, two studies reported that debriefing was associated with an increased risk of PTSD (Bisson et al, 1997;Hobbs et al, 1996). At this date, the recommendation in the scientific literature is not to conduct such interventions (McNally, Bryant, and Ehlers, 2003;Nash and Watson, 2011;Rose et al, 2002).…”
Section: Psychological Debriefingmentioning
confidence: 99%
“…Bisson et al (1997) randomly assigned recently hospitalized burn victims to either debriefing or to an assessment only control condition. Although there were no significant differences between groups at the 3-month evaluation, at the 13-month evaluation, the rate of PTSD was significantly higher among debriefed patients than among control patients (26 vs 9%) and debriefed participants had significantly higher scores on self-report measures of PTSD, anxiety, and depression.…”
Section: Psychological Debriefingmentioning
confidence: 99%